2016
DOI: 10.4209/aaqr.2016.01.0043
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bioaerosols and their Relation with OC, EC and Carbonyl VOCs at a Busy Roadside Restaurants-Cluster in New Delhi

Abstract: Measurement of biological particles (bioaerosols) in ambient air is of great importance as it is directly linked with the health issues. However, data on the bioaerosols characterization are scarce. Here we report on the concentration and characterization of bioaerosols (including bacterial and fungal aerosols) as well as determination of organic and elemental carbon (OC and EC) in total suspended particulate matter (TSPM) at a busy roadside restaurants-cluster site in New Delhi. In addition, 14 carbonyl volat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…It has been demonstrated that wearing facemasks for a long time can reduce the probability of infection from influenza-like illnesses (MacIntyre et al, 2009;Natarajan et al, 2016;Lin et al, 2017). Especially, functional facemasks are recommended for frontline healthcare workers to prevent splashes and sprays of blood, body fluids and the spread of infection from the wearer (Siegel et al, 2007;Agarwal et al, 2016). At present, polypropylene (PP) melt-blown nonwoven fabric has been extensively employed as a filter for biological protective respirators because it resists microparticles and pathogenic microorganisms based on physical effects.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that wearing facemasks for a long time can reduce the probability of infection from influenza-like illnesses (MacIntyre et al, 2009;Natarajan et al, 2016;Lin et al, 2017). Especially, functional facemasks are recommended for frontline healthcare workers to prevent splashes and sprays of blood, body fluids and the spread of infection from the wearer (Siegel et al, 2007;Agarwal et al, 2016). At present, polypropylene (PP) melt-blown nonwoven fabric has been extensively employed as a filter for biological protective respirators because it resists microparticles and pathogenic microorganisms based on physical effects.…”
Section: Introductionmentioning
confidence: 99%
“…Rural houses in present study are comparatively heavily crowded with 5e6 peoples of different age group, health and gender. Therefore, constant human activities of different background people and their activities like burning of oil lamps and incense can cause bacterial emissions (Agarwal et al, 2016). In present study, higher fungal load has been observed in rural houses probably attributed to the outdoor fungal sources such as agricultural activities and cattle sheds (Fig.…”
Section: Bioaerosol Concentration In Urban and Rural Environmentmentioning
confidence: 49%
“…Identified Bacillus species in PM 2.5 can survive long in the air and known to cause food poisoning and periodontal disease (Agarwal et al, 2016). Prevalence of similar bacteria aerosols in indoor environments were also reported in previous studies (Agarwal et al, 2016;Sheikh et al, 2015;Gangamma et al, 2011). Among 7 identified species of airborne fungi (Aspergillus sp., Cladosporium sp., Penicillium sp., Alternaria alternata, Fusarium sp., Trichoderma sp.…”
Section: Microbial Identificationmentioning
confidence: 56%
See 1 more Smart Citation
“…It should be noted that for different microorganisms (strains, genera, kingdoms), these dynamics can vary significantly. In particular, in many cases, the concentration of culturable bacteria in a warm season is higher than in a cold one [75][76][77][78][79][80][81][82][83][84][85][86], but there are also opposite examples [80,[87][88][89][90][91].…”
Section: Discussionmentioning
confidence: 99%